Daytime F Region Echoes at Equatorial Ionization Anomaly Crest During Geomagnetic Quiet Period: Observations From Multi‐Instruments - Yi Liu; Zhongxin Deng; Tong Xu; Jian Kong; Chen Zhou; Yibin Yao; Qiong Tang; Zhengyu Zhao (Space Weather)
Abstract By using Qujing very high frequency radar (25.6°N, 103.7°E, magnetic latitude 16.1°N, magnetic longitude 177.0°E), daytime F region echoes were reported at equatorial ionization anomaly crest on 26 June 2020. Radar interferometry experiment was performed during the observation period. The observed results show that the spatial distributions of daytime F region echo pattern were about 150 km, 200 km, and 180 km in the zonal, meridional, and height extents, respectively. In addition, we observed a remarkable eastward drift of F region echoes with a mean velocity of about 50 m/s. To investigate the possible generation mechanism of daytime F region echoes, simultaneous occurrences of ionospheric disturbance and atmospheric gravity wave activities were presented by combining with the observations of ionosonde, global position system stations and FY‐4A satellite. The existence of gravity wave from the deep convective activities in the lower atmosphere was confirmed by using FY‐4A satellite measurements. The gravity wave signatures were also observed in the time series of virtual height deviations of sporadic E (dhES) and total electron content near the region where the F region echoes. We surmise that ionospheric disturbance in the F region could be excited during atmospheric gravity wave activities. Then the large‐scale ionospheric disturbance could further evolve into small‐scale irregularity producing radar echoes through the non‐linear cascade process.